Descriptive Strength and Range of Motion in Youth Baseball Players - Ross M Nakaji; Todd S Ellenbecker; Kevin M McClenahan; Lianna M Roberts; Chase Perez; Scott B Dickenson (International Journal of Sports Physical Therapy)
# Background There are limited studies reporting descriptive strength and range of motion in youth baseball players 12 years of age or younger.